2013
DOI: 10.1371/journal.pone.0064788
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Baroreceptor Reflex Counteracts Long-Term Blood Pressure Increase in the Rat Model of Renovascular Hypertension

Abstract: IntroductionThe present study tested the hypothesis that long-term effects of baroreceptor activation might contribute to the prevention of persistent arterial blood pressure (BP) increase in the rat model of renovascular hypertension (HTN).MethodsRepetitive arterial baroreflex (BR) testing was performed in normo- and hypertensive rats. The relationship between initial arterial BR sensitivity and severity of subsequently induced two-kidney one-clip (2K1C) renovascular HTN was studied in Wistar rats. Additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 36 publications
(39 reference statements)
2
8
0
1
Order By: Relevance
“…Reports in the literature have suggested an association between baroreflex dysfunction and sympathetic overactivity, with subsequent development of hypertension . A different model, investigating the effects of a maternal obesogenic diet on offspring at 30 and 90 days of age, demonstrated that an obesogenic diet was able to induce high BP, autonomic imbalance, impaired baroreflex mechanism in 90 day‐old animals, suggesting that the sympathetic overactivity and hypertension in that model was due to baroreflex dysfunction, as also shown in other studies . So one of the hypotheses tested in our study was that the BR dysfunction might be involved in the onset of the hypertension in animals subjected to perinatal protein malnutrition.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Reports in the literature have suggested an association between baroreflex dysfunction and sympathetic overactivity, with subsequent development of hypertension . A different model, investigating the effects of a maternal obesogenic diet on offspring at 30 and 90 days of age, demonstrated that an obesogenic diet was able to induce high BP, autonomic imbalance, impaired baroreflex mechanism in 90 day‐old animals, suggesting that the sympathetic overactivity and hypertension in that model was due to baroreflex dysfunction, as also shown in other studies . So one of the hypotheses tested in our study was that the BR dysfunction might be involved in the onset of the hypertension in animals subjected to perinatal protein malnutrition.…”
Section: Discussionsupporting
confidence: 79%
“…14 and 90 days of age, demonstrated that an obesogenic diet was able to induce high BP, autonomic imbalance, impaired baroreflex mechanism in 90 day-old animals, 28 suggesting that the sympathetic overactivity and hypertension in that model was due to baroreflex dysfunction, as also shown in other studies. 21,29,30 So one of the hypotheses tested in our study was that the BR dysfunction might be involved in the onset of the hypertension in animals subjected to perinatal protein malnutrition. To test this, we applied different doses of vasoactive drugs, to provide different levels of activation and inhibition of the BR.…”
Section: Discussionmentioning
confidence: 98%
“…The baroreflex is one of the most powerful and rapidly acting mechanisms for controlling arterial BP. It has been suggested that arterial baroreflex is involved in the long-term control of BP [ 30 ]. Several studies have shown that the sensitivity of the baroreflex is diminished in several forms of hypertension [ 22 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the relationship between maternal protein restriction and sympathetic overactivity have been suggested (Johansson et al, 2007 ; Franco et al, 2008 ; Barros et al, 2015 ), less is known about the physiological dysfunctions responsible for producing these effects. In this context, it is described that a baroreflex dysfunction could lead to a sympathetic overactivity and subsequent development of hypertension (Souza et al, 2001 ; Heusser et al, 2010 ; Tsyrlin et al, 2013 ). However, the hypothesis that maternal protein restriction leads to baroreflex dysfunction has not been proved yet.…”
Section: New Insights On the Perinatal Origin Of Hypertension: The Romentioning
confidence: 99%